Schisandrin Attenuates Lipopolysaccharide-Induced Lung Injury by Regulating TLR-4 and Akt/FoxO1 Signaling Pathways - Sun, Kai; Huang, Rong; Yan, Li; Li, Dan-Tong; Liu, Yu-Ying; Wei, Xiao-Hong; Cui, Yuan-Chen; Pan, Chun-Shui; Fan, Jing-Yu; Wang, Xian; Han, Jing-Yan (Frontiers in Physiology, 2018)
Objective: Acute lung injury is a severe clinic condition with limited therapeutic approaches. This study evaluated whether schisandrin (Sch), an ingredient of Schisandra chinensis, has preventive effects on endothelium and epithelium injury induced by lipopolysaccharide (LPS) and the underlying mechanisms. Methods: Male Wistar rats were continuously infused with LPS (5 mg/kg/hr) via the left jugular vein for 90 min. In some rats, Sch (2.5 mg/kg//hr) was administrated through the left jugular vein 30 min before LPS infusion. Leukocyte recruitment, levels of inflammatory cytokines, lung histology and edema, vascular and alveolar barrier disruption and related proteins were evaluated at indicated time point after LPS challenge. Results: LPS infusion for 90 min resulted in an increased leukocyte adhesion to pulmonary venules and overproduction of cytokine and chemokine in both serum and lung homogenate. At eight hours after termination of LPS infusion, obvious Evans blue extravasation and lung edema were observed, along with an increased apoptosis, a decreased expression of tight junction and adherent junction proteins, and a reduction in vWF and keratin, all of which were attenuated by Sch treatment. Meanwhile, the LPS-elicited activation of TLR-4/NF-κB/MAPK and FoxO1 signaling was inhibited by Sch. Conclusions: The present study revealed that pretreatment with Sch alleviated lung endothelium and epithelium injury after LPS stimulation, which is attributable to inhibition of cell injury and activation of cell regeneration via regulation of TLR-4/NF-κB/MAPK and Akt/FoxO1 signaling pathway.